2009
DOI: 10.1002/glia.20935
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of relapsing–remitting and chronic forms of experimental autoimmune encephalomyelitis in C57BL/6 mice

Abstract: Multiple sclerosis (MS) is an autoimmune, demyelinating disease of the central nervous system (CNS). Like MS, the animal model experimental autoimmune encephalomyelitis (EAE) is characterized by CNS inflammation and demyelination and can follow a relapsing-remitting (RR) or chronic (CH) disease course. The molecular and pathological differences that underlie these different forms of EAE are not fully understood. We have compared the differences in RR- and CH-EAE generated in the same mouse strain (C57BL/6) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 69 publications
7
120
0
2
Order By: Relevance
“…In comparison, investigations based on the use of C57Bl/6 mice, also sensitive to the same encephalitogenic peptide, have been facilitated by a vast array of transgenic and gene deletion mutants. However, the use of the C57Bl/6 variant is complicated by the occurrence of multiple clinical profiles (chronic, multiphasic or monophasic) and unpredictability of disease course within a given cohort (Berard et al 2010;Bernard et al 1998). Additionally, we have shown that the pathology in this variant is associated with a progressively diminishing astrogliosis with increasing clinical score, a feature which is not associated with MS pathology (Ayers et al 2004;Onuki et al 2001;Pham et al 2009Pham et al , 2011Wang et al 2005).…”
Section: Future Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In comparison, investigations based on the use of C57Bl/6 mice, also sensitive to the same encephalitogenic peptide, have been facilitated by a vast array of transgenic and gene deletion mutants. However, the use of the C57Bl/6 variant is complicated by the occurrence of multiple clinical profiles (chronic, multiphasic or monophasic) and unpredictability of disease course within a given cohort (Berard et al 2010;Bernard et al 1998). Additionally, we have shown that the pathology in this variant is associated with a progressively diminishing astrogliosis with increasing clinical score, a feature which is not associated with MS pathology (Ayers et al 2004;Onuki et al 2001;Pham et al 2009Pham et al , 2011Wang et al 2005).…”
Section: Future Studiesmentioning
confidence: 98%
“…Low incidence ≤50 %, moderate incidence = 50-65 %, high incidence = 65-85 %, very high incidence ≥85 % MOG, encompassing the extracellular domain (amino acids 1-122), is encephalitogenic in the following mouse strains: Biozzi AB/H (chronic-relapsing profile [Smith et al 2005]), C57Bl/6 [variable profile, depending on immunization protocol (Berard et al 2010;Bernard et al 1998)], NOD/Lt [chronic-relapsing profile , as well as the Lewis and Dark Agouti rats [predominantly chronic-relapsing profile (Johns et al 1995;Storch et al 1998b)] and Brown Norway rat [hyperacute profile (Stefferl et al 1999)], and non-human primate species including the rhesus monkey Macaca mulatta [predominantly hyperacute profile ] and the common marmoset Callithrix jacchus [chronic-relapsing profile (Merkler et al 2006)]. Clinical disease is associated with severe demyelination in all of these species/strains, except that in the Biozzi AB/H mouse strain demyelination is very mild in the first attack, and severe only in the relapse phase (Smith et al 2005 (Amor et al 1994).…”
Section: Mog-induced Eae An a Model For Msmentioning
confidence: 99%
“…Dysregulation of SOCS expression has been implicated in several inflammatory diseases, including models of multiple sclerosis (65)(66)(67)(68)(69), rheumatoid arthritis (70,71), systemic lupus erythematosus (72,73), psoriasis (74,75), type 1 diabetes (51, 76 -79), sepsis (80,81), and also in human allergic disease (82)(83)(84). Furthermore, deficiencies in SOCS1 expression have been observed in the smooth muscle in airways (85), and epithelial cells (86) of asthmatic patients and functional SOCS1 polymorphism have been correlated with the development of adult onset asthma and increased IgE levels (87,88).…”
Section: Socs1 Regulates Il-4-induced Irs-2 Signaling In Human Monocytesmentioning
confidence: 99%
“…Sildenafil effects on remyelination were further studied by curpizone demyelination model, showing as well a significant amelioration of clinical symptoms associated with a protective effect on myelin structure, reduction of reactive gliosis (microglia and astrocytes) and decreased expression of pro-inflammatory cytokines (Nunes et al 2012). Furthermore, treatment with sildenafil starting at the onset of EAE has shown to prevent the disease progression, to maintain myelin and axon structure, decrease microglial activation, down-regulate the innate and adaptative responses decreasing pro-inflammatory cytokine production and proliferation in splenocyte, and has shown to upregulate the alternative 82 microglia/macrophage activation marker Ym-1 associated with neuroregenerative effects (Pifarre et al 2014 (Berard et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In order to study more specifically sildenafil effects on microglia/macrophage phenotype BMDM cultures were established. The study of these cells grants clinical significance since EAE model as well as in MS peripheral immune cell infiltrates can be found (Berard et al 2010, Henderson et al 2009). …”
Section: Discussionmentioning
confidence: 99%